2017
DOI: 10.1590/s1517-707620170002.0179
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of waste paper and rice hulls as filler in polymeric matrix composites

Abstract: Concerns for the environment are recurrent in our society, and research on low impact materials such as those produced from waste is an alternative. This work is based on the reuse of scrap paper and rice hulls aiming to increase the life cycle of these waste products and to find better destination. Composites with a volumetric filler content (dispersed phase) of 80% were produced via compression molding using polyurethane (PU) based on castor oil or polyester resin as matrix, in four distinct families: polyes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…PU/WP composites have only been reported recently. The first work reported PU and polyester mixed with WP and rice hulls, considering 80 v / v % of filler from which the composite plates were produced by compression molding [ 96 ]. The results showed that PU/WP presented the best water resistance performance.…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…PU/WP composites have only been reported recently. The first work reported PU and polyester mixed with WP and rice hulls, considering 80 v / v % of filler from which the composite plates were produced by compression molding [ 96 ]. The results showed that PU/WP presented the best water resistance performance.…”
Section: Waste Paper-polymeric Compositesmentioning
confidence: 99%
“…Other researchers concluded that ramie addition positively affected the mechanical properties of polyester matrix composites whereas effect of cotton fibers remained limited [20]. The results found in literature clearly show that the mechanical properties are a result of the combination of the type, content and state of prior chemical treatment of the reinforcement fibers and the type of the polymer matrix used to produce the composites [15,21].…”
Section: Introductionmentioning
confidence: 94%
“…In addition to this, the difference in the interaction of the filler fibers with the matrix polymer also affects the tensile strengths of the samples. Calegari et al [21] stated that tensile strength of the samples changed with the matrix polymer material where the same filler materials cause different effects on the tensile strength values in the same polymer matrix.…”
Section: Mechanical Testingmentioning
confidence: 99%
“…Fibers are commonly used as reinforcing materials in composite applications because of their high aspect ratios which provide high tensile strength and other material properties. Wastepaper (WP) was used as a filler in samples of polyester (P) and polyurethane (PU) as a matrix, with matrix to filler ratio of 20:80 [12]. The tensile strength for the P/WP composite reduced from 17.8±0.5 MPa to…”
Section: Composite Reinforcementmentioning
confidence: 99%